Environmental and administrative EVIAVE-based approach for landfill siting - Avelino, Catarina (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2019)
Landfill site selection is a relevant and necessary issue for waste management. However, it is an extremely complex task since it must take into account different environmental, economic and socio-political criteria that need to comply with strict regulations and meet different opinions. Accordingly, in this paper we propose a multi-criteria EVIAVE-(Evaluación del impacto ambiental en vertederos) based approach to evaluate the suitability of a set of possible landfill locations and rationally provide an optimal location for a landfill. The approach requires a comprehensive analysis to identify the best feasible site(s) that minimize a Global Landfill Risk Index (GRI), focused on environmental, economic and administrative impacts, and simultaneously comply with governmental regulations and constraints. This GRI is based on the Environmental Landfill Index, Administrative Landfill Index, Environmental Risk Index, Environmental Value, Probability of Contamination and Contamination Risk Index. An innovative feature of this approach lies in incorporating a mathematical model that combines weighted environmental and administrative issues. The model not only provides an optimal landfill location but also establishes landfill location ranks according to indexes of interest. This methodology reveals flexibility and high adaptability, being a useful and effective tool in the decision-making process. The methodology presented was tested with data available from a preliminary study developed in the municipalities of Oporto Metropolitan Area, Portugal, for the implementation of a multi-municipal landfill, which considers nine different locations for analysis